Exploring methodological approaches to assess climate change vulnerability and adaptation: reflections from using life history approaches - Ansah, P.; Singh, C.; Tebboth, M.; Spear, D.; Mensah, A. (Regional Environmental Change, 2019)
People in developing countries face multiple risks, and their response decisions sit at the complex and often opaque interface of climatic stressors, constrained resource access, and changing livelihoods, social structures, and personal aspirations. Many risk management studies use a well-established toolkit of methodologies—household surveys, focus group discussions, and semistructured interviews.We argue that such methodological conservatism tends to neglect the dynamic and differentiated nature of livelihood decisions. Since different methodologies privilege different portrayals of risk and response, we highlight how plural methodological approaches can capture a broader range of perspectives and problematisations. In this paper, we draw on life history (LH) interviews across four countries (Kenya, Namibia, Ghana, and India) to offer one way of expanding current methodological approaches on vulnerability and adaptation. We argue that LHs offer four key ‘value additions’. First, LHs give insights into the multiple and interacting nature of drivers of response behaviour. Second, they highlight intra-household dynamics to demonstrate how people with differential power shape risk management decisions. Third, LHs support explorations of past decisions, present situations, and future aspirations, thus producing temporally nuanced enquiries. Fourth, they provide a powerful analytical lens to capture the interplay of motivations, aspirations, and values on livelihood choices and adaptation outcomes. By adding value in these four ways, LHs challenge assumptions about how and why people respond to multiple risks and offer a nuanced understanding of adaptation processes.
Research Article
Keywords: Life histories; Adaptation; Migration; Livelihoods; Vulnerability; Temporality; Riskperception; Riskmanagement